Nervous Acts - Rousseau, G. author. aut Link
XII, 395 p.
Keywords: These essays demonstrate the sweeping influence of the human nervous system on the rise of literature and sensibility in early modern Europe. The brain and nerves have usually been treated as narrow topics within the history of science and medicine. Now George Rousseau, an international authority on the relations of literature and medicine, demonstrates why a broader context is necessary. The nervous system was a crucial factor in the rise of recent civilization. More than any other body part, it holds the key to understanding how far back the strains and stresses of modern life - fatigue, depression, mental illness - extend.